LOCAL DISTRIBUTION AND COEXISTENCE OF PREVALENT TREE SPECIES IN PEAT SWAMP FORESTS OF CENTRAL KALIMANTAN - Herwint Simbolon (BRIN Publishing (Penerbit BRIN), 2009)
SIMBOLON, H. 2009. Local Distribution and coexistence of prevalent tree species in peat swamp forests of Central Kalimantan. Reinwardtia 12(5): 373–382 -A study on the distribution and coexistence of prevalent tree species in peat swamp forests was conducted at Lahei and Kelampangan, Central Kalimantan. The prevalent species in both sites were Calophyllum canum, Combretocarpus rotundatus, Cratoxylum glaucum, Ctenolophon parvifolius, Elaeocarpus petiolatus, with Palaquium cochleariifolium at Kelampangan, and Buchanania sessifolia, Madhuca sericea, Semecarpus sp., Shorea balangeran, Tetractomia obovata and Vatica oblongifolia at Lahei plot. The prevalent species were randomly distributed, however, when individuals were grouped into mature vs juvenile, the mature individuals of C. parvifolius tended to be clumped and the juvenile were randomly distributed; while in C. rotundatus, the mature individuals were randomly distributed and the juvenile were clumped. Pattern of the coexistence among the prevalent species in the study site were associated, and independent relationships, and almost no exclusion relationship was found. Independent and associated relationships among the coexisting species may be one of the explanations of the mechanism which maintain relatively high diversity of plant species in the tropical peat swamp forests, which has extreme habitat conditions and narrow habitat heterogeneity. Pattern of the coexistence relationships among mature vs juvenile individuals of the same species varied.